Association between triglyceride glucose index and hyperuricemia: a new evidence from China and the United States - Gou, Ruoyu; Dou, Danni; Tian, Mi; Chang, Xiaoyu; Zhao, Yonggang; Meng, Xin; Li, Guanghua (Frontiers in Endocrinology, 2024)
Background: Hyperuricemia (HUA) is a global public health problem. The etiology of HUA is complex and efficient and accurate assessment metrics are still lacking when conducting large-scale epidemiologic screening. The aim of this study was to evaluate the association of the triglyceride glucose (TyG) index, TyG-body mass index (BMI), TyG-waist-to-height ratio (WHtR) with the risk of HUA. Methods: Based on data collected from the National Health and Nutrition Examination Survey (NHANES) in the United States and the China Health and Aging Longitudinal Study (CHARLS) in China, a total of 14,286 U.S. adults and 4,620 Chinese adults were included in the analysis. The study examined the levels of TyG, TyG-BMI, TyG-WHtR, and TyG-WC. Multivariate logistic regression was utilized to investigate the relationships between these variables and hyperuricemia (HUA), separately. Additionally, the study used restricted cubic splines (RCS) to explore the linear associations of TyG, TyG-BMI, TyG-WHtR, TyG-WC, and HUA, separately. Results: The NHANES results showed that TyG (Q2, 1.58(1.26, 1.98); Q3, 2.36 (1.94, 2.88); Q4, 3.21 (2.61, 3.94)), TyG-BMI (Q2, 2.14 (1.74, 2.65); Q3, 3.38 ( 2.74, 4.17); Q4, 6.70 (5.55, 8.02)), TyG-WHtR (Q2, 1.92 (1.56, 2.36); Q3, 3.14 (2.56, 3.85); Q4, 6.28 (5.12, 7.69)), TyG-WC (Q2, 2.32 ( 1.85, 2.90); Q3, 3.51 (2.84, 4.34); Q4, 7.32 (5.95, 9.02)) were identified as risk factors for hyperuricemia (HUA). Similarly, the CHARLS results, when fully adjusted for covariates, indicated that TyG (Q4, 2.36 (1.08, 5.15)), TyG-BMI (Q3, 2.60 (1.05, 6.41); Q4, 3.70 (1.64, 8.32)), TyG-WHtR (Q4, 2.84 (1.23, 6.55), TyG-WC (Q4, 2.85 (1.23, 6.5)) were also risk factors for HUA. The predictive ability of each indicator for the risk of developing HUA was stronger in women than in men. Furthermore, there was an observed nonlinear relationship between TyG, TyG-BMI, TyG-WHtR, TyG-WC, and HUA in both the NHANES and CHARLS datasets (P-nonlinearity < 0.05). Conclusion: These findings suggest that TyG, TyG-BMI, TyG-WHtR and TyG-WC are associated with an increased risk of HUA. They are potential indicators for screening HUA status in the general population in China and the United States.